A study of the development of vegetation type map using visual image interpretation technique - Shankar Patel; Acharya Patnaik; Omkar Sanjeev Ashok; Gulati Goyal Goswami (African Journal of Environmental Economics and Management, 2015)
Rajasthan, the largest state of India has a geographic area of 342,239 km2; shows great variation in climate and vegetation. In the present study, vegetation types and land use of Rajasthan were mapped using multi-season IRS P6 LISS III data. Visual image interpretation technique was adopted in mapping the heterogeneity of land cover classes at 1:50,000 scale. Georeferenced phytosociological information was also used to delineate different vegetation formations. Altogether 26 vegetation type classes were mapped in the study region. The vegetation cover occupies 16.78% of the geographical area of the State. Of the total vegetation cover, forest area is contributing 4.71% of the geographical area. The main forest types of Rajasthan includes Dry Deciduous forest, Thorn forest, Broad leaved hill forest, Dhauk forest, Teak mixed forest and Riverine forest. The vegetation type map prepared provides a key input for biodiversity understanding at landscape level.